(untitled) (Ustozlar uchun, 2026)
Translating historical texts poses unique challenges, particularly in preserving the archaic style, tone, and rhetorical devices of the source language. This article examines strategies employed by translators to maintain the stylistic and aesthetic qualities of Uzbek historical literature in English translation. Using selected excerpts from Yulduzli tunlar, the study analyzes how archaic vocabulary, metaphors, and narrative tone are rendered in the target language. The findings show that strategies such as semantic approximation, syntactic restructuring, paraphrasing, and stylistic compensation are commonly used to balance readability with fidelity to the original style. The study concludes that successful translation of historical texts requires careful attention to both linguistic and stylistic features, ensuring that the target text reflects the aesthetic and historical essence of the original.